(untitled) (Journal of Medicine, 2009)
Gigantism came from Greek word âGiant’. Pathologically, this condition results from the actions of excessive growth hormone (GH) secretion from the pituitary gland during childhood and adolescent before the closure of epiphyseal growth plates. When the height of an individual is several standard deviations above the mean value for the same age, sex, and ethnicity, the condition is known as gigantism. Pituitary gigantism is extremely rare. If hypersecretion of growth hormone occurs after closure of epiphyseal growth plates the resulting condition is acromegaly. Most patients with gigantism also have features of acromegaly. Â doi:10.3329/jom.v10i1.1999 J Medicine 2009; 10: 22-24